Outcome of the Quota Formula Review : Report of the Executive Board to the Board of Governors. (Policy Papers; Policy Paper, 2013)
In completing the Fourteenth General Review of Quotas and approving the Proposed Amendment on the Reform of the Executive Board, the Board of Governors requested that the Executive Board complete a comprehensive review of the quota formula by January 2013. The Executive Board was also requested to bring forward the timetable for completion of the Fifteenth General Review of Quotas (hereafter the 15th Review) to January 2014.